On the design of stiffened steel plate shear wall with diagonal stiffeners considering the crack effect. (June 2021) - Khaloo, Alireza; Ghamari, Ali; Foroutani, Maryam
Abstract: Steel Plate Shear Walls (SPSWs) have high stiffness, strength, and considerable energy absorption capability, which have persuaded engineers to utilize the system in their practical projects. Some significant characteristic SPSWs have remained unknown despite worthwhile experimental and numerical studies. One of these unknown aspects is the effect of cracks on SPSWs behavior. Various experimental studies have reported the fracture of SPSWs during testing due to crack growth, but none of the experimental tests have studied the crack effect. In this respect, the behavior of SPSWs strengthened with diagonal stiffeners is studied in this paper. To study this, cracks located at the intersection of stiffeners (based on experimental reports) were investigated. Numerical results show that stiffened walls exhibit higher properties compared to SPSWs in both elastic and inelastic zones. It is also concluded that thicker stiffness enhances the seismic parameters of SPSWs (stiffness, energy absorption, capacity). The results also show that unlike walls without stiffeners, in which the presence of cracks causes the destruction of the wall, in stiffened walls the stiffeners prevent severe destruction of the wall with the presence of cracks. The effect of crack was also introduced as a mathematical equation to estimate the load–displacement curve. Proposed equations show a good correspondence with the finite element results.